Revision of Madagascan Cleridae (Coleoptera: Cleroidea). Part I.—The genus Biflabelotillus Pic, 1949 (Tillinae) - Pavel, Filip; Purchart, Luboš (Zootaxa, 2024)
The genus Biflabelotillus Pic, 1949 is reviewed and a new species B. bicolorus sp. nov. is described. The female of Biflabelotillus peyrierasi Menier, 1979 is reported with remarks on the sexually dimorphic morphology and colour variation. Lectotype is designated for Biflabelotillus foveolatus Pic, 1949. Photographs of habitus and significant morphological features, new faunistic data and a key to the species are provided.